INTERACTIVE MEDIA DEVELOPMENT FOR SECOND GRADE ELEMENTARY STUDENTS THEMATIC LEARNING USING ADOBE FLASH CS4 PROFESSIONAL - Nugraha, R. Gita Ardhy (Program Studi Pendidikan Guru Sekolah Dasar, Universitas Kristen Satya Wacana, 2017)
Interactive media can be used to support the thematic learning process. From the observation on second grade Satya Wacana Christian Elementary School, it was found that second gradeâs teacher did not use interactive media to support thematic learning. Students were lack of interest to learn. Because of this problem, an interactive media is developed as a new way to support the thematic learning process. The aim of this study is to describe the appropriateness of interactive media based on Adobe Flash CS4 Professional and the effect of interactive media implementation in the 2013th Curriculum thematic learning process. The method in this study is research and development. The result showed that interactive media was proper to use as learning media in the thematic learning process based on expert test score (3,83 & 3,23). Interactive media has a very good value based on field test score (4,24 & 4,26). Using interactive media affected studentâs interest and motivation. The media also given attractiveness and effectiveness in the thematic learning process based on the questionnaire by students and second gradeâs teachers.Â